Predictive ability of problem-solving efficacy sources on mathematics achievement - Januard D. Dagdag; Noel A. Palapuz; Nikka A. Calimag (Institute of Advanced Engineering and Science, 2021)
This study examined the relationship between mathematics achievement and mathematics problem-solving efficacy sources. A cluster sample of 123 first year prospective teachers of a Philippine higher education institution responded to a 30-item problem-solving efficacy scales and took the teacher-made tests in Mathematics in the Modern World course; namely, Non-Routine Problem Solving and Natures and Numbers Pattern Tracing (NRPS-NNPT), Math Language and Symbols (MLS), and Data Management (DM). The research data was analyzed using Descriptive statistics, Pearson-r and Standard Multiple Regression. On the average, the respondents had satisfactory mathematics achievement. They reported a high level of social persuasion and somatic response and a low level of vicarious experience and mastery experience in mathematics problem-solving. Vicarious experience was directly associated with mastery experience while social persuasion and mastery experience were both inversely related to somatic responses. Among the four problem-solving efficacy sources, only social persuasion significantly predicted mathematics achievement specifically in the areas of NRPS-NNPT, MLS, and DM. Thus, becoming a trusted voice of encouragement and designing a persuasive and optimistic learning environment are highly recommended roles of schools to facilitate students’ mathematics achievement.